Studi Eksplorasi Faktor yang Mempengaruhi Keberlanjutan Pemakaian Layanan Mobile Payment - Alfian Tan; Paulina Kus Ariningsih; Cherish Rikardo (The Industrial Engineering Department of Engineering Faculty at Universitas Andalas, 2020)
This research explores some potential factors that affect the continuance intention of a mobile payment service. The trend of mobile payment services has been increasing since the last few years. The advancing technology of the internet and smartphone has been a supporting environment for the growth of this method. Many similar mobile payment services are offered in the community which results in a highly competitive business condition. The business owner who has put a high investment in this business will surely want to keep it running and even grow their product. Therefore, some knowledge of factors that can significantly promote the sustained use of their product to customers will be imperative. In this research, some existing models on the general repurchase intention concept and users’ continuance intention will be combined and tested to figure out some influential aspects to continuance intention concept. Seven factors are hypothesized to have direct and indirect effects. Data from 193 respondents are gathered and the results of the tested model shows perceived quality, perceived value, and brand preference subsequently influence the continuance intention. Further analysis is also conducted in this research to explain the relationship between factors as well as analysis of current mobile payment providers.